THE TRANSMISSION PROBLEM WITH TIME DEPENDENT COEFFICIENTS WITH NONLINEAR INTERNAL DAMPING - Cabanillas Lapa, Eugenio (2008)
In this paper we consider the nonlinear transmission problem for the wave equation with time dependent coefficients and nonlinear internal damping. We prove global existence and study decay properties of the solutions. The result is achieved by using the multiplier technique and suitable unique continuation theorem for the wave equation.